RELASI AGAMA DAN NEGARA: TELAAH HISTORIS DAN PERKEMBANGANNYA - Muhammad Anang Firdaus (Harmoni, 2014)
The relationship between religion and the state is an issue that is continually discussed. This paper outlines the historical development of political systems in the Islamic world since the early Islam, from its glory to its decline. Ijtihad of the Muslim scholars (Ulema) on this matter can be divided into three distinct streams. In the first stream, religion must order all aspects of life including political affairs and the state. In the second stream, religion is seen to be completely separate from the state. In the third stream, Islam is a set of ethical values for the life of the state. In the Indonesian context, conflict about the relationship between religion and state was present at the beginning of independence, but was partially resolved when the Founding Fathers agreed on the relationship between religion and state in the Republic of Indonesia.